Russian-Persian Economic Relations in Early 20th Century: Road Construction - G. G. Kornoukhova (Научный диалог)
This article explores the history of the construction of one of the main transportation arteries in modern Iran: the Enzeli-Teheran highway with the Kazvin-Hamadan section. The road was funded by the Russian treasury and aimed to boost Russian-Persian trade by including not only the northern provinces of Persia but also the central part of the country. The intensification of trade was expected to occur through the introduction of automobile traffic on the highway, replacing the archaic caravan routes. The article presents the perspectives of both the Russian government of that period and entrepreneurial circles on the choice of road direction and the justification for transitioning to a new method of cargo delivery. It concludes that there were significant discrepancies in the positions of these parties. While the Russian government saw great geopolitical advantage in connecting the largest Enzeli port with Teheran and constructing the Kazvin-Hamadan branch linking northern Persia with its central part, entrepreneurs viewed it as a threat of European product penetration into northern Persia. Fortunately, the entrepreneurial community was not unanimous in its views, and a group emerged willing to embark on this new venture, promising to be successful and give a fresh impetus to Russian-Persian trade relations.